Tumor-Infiltrating Immune Cells Promoting Tumor Invasion and Metastasis: Existing Theories - Man, Yan-gao (Ivyspring International Publisher, 2013)
It is a commonly held belief that infiltration of immune cells into tumor tissues and direct physical contact between tumor cells and infiltrated immune cells is associated with physical destructions of the tumor cells, reduction of the tumor burden, and improved clinical prognosis. An increasing number of studies, however, have suggested that aberrant infiltration of immune cells into tumor or normal tissues may promote tumor progression, invasion, and metastasis. Neither the primary reason for these contradictory observations, nor the mechanism for the reported diverse impact of tumor-infiltrating immune cells has been elucidated, making it difficult to judge the clinical implications of infiltration of immune cells within tumor tissues. This mini-review presents several existing hypotheses and models that favor the promoting impact of tumor-infiltrating immune cells on tumor invasion and metastasis, and also analyzes their strength and weakness.